POLITICAL MANAGEMENT AS AN INFORMATION AND COMMUNICATION REGULATION PROCESS OF MODERN PUBLIC RELATIONS - S V Volodenkov (RUDN Journal of Political Science, 2017)
The article focuses on issues related to the analysis of the modern political communication management nature. The paper demonstrates the nature of the basic elements of communication management processes in the sphere of politics. The article also shows the transition from the classical subject-object model in the field of public relations management to a new subject-subject model of information and com-munication interaction at the horizontal level, in which the strongest influence on all stages of the man-agement process have values and meanings, which are products of communication relations. The study concluded that in contemporary information society communication basis of political management becomes crucial condition for the implementation of all management processes, defining the content and parameters of the key features of the functioning of the state, its stability and success.